A functional coating to enhance antibacterial and bioactivity properties of titanium implants and its performance in vitro - Doymus, Burcu; Kerem, Gizem; Yazgan Karatas, Ayten; Kok, Fatma Nese; Onder, Sakip (SAGE PUBLICATIONS LTD, 2021)
Bacterial infections and lack of osseointegration may negatively affect the success of titanium (Ti) implants. In the present study, a functional coating composed of chitosan (CS) microspheres and nano hydroxyapatite (nHA) was prepared to obtain antimicrobial Ti implants with enhanced bioactivity. First, the chitosan microspheres were fixed to Ti surfaces activated by alkali and heat treatment, then nHA coatings were precipitated onto these surfaces. Ciprofloxacin was loaded into the microspheres using two different procedures; encapsulation and diffusion. Scanning electron microscopy micrographs of the modified Ti surfaces showed that the coating was successfully deposited onto the Ti surfaces and stable for 30 days in PBS. The drug was completely released from free microspheres loaded by encapsulation in 21 days whereas only 89% release was observed after immobilization. The burst release also decreased from ca. 55% to ca. 35%. The release was further reduced following the nHA precipitation. The modified Ti surfaces showed antimicrobial activity based on the bacterial time-kill assay using S. aureus, but the efficiency was affected by both nHA precipitation and drug loading strategy. Highest antimicrobial activity was seen in the samples without nHA layer, and when the drug was loaded by diffusion. Fourier transform infrared spectroscopy and X-ray diffraction analyses revealed that nHA on the surface enhanced HA growth in simulated body fluid for 3 weeks, showing increased osseointegration potential. Therefore, the proposed coating may be used to prevent Ti implant failure originated from bacterial infection and/or low bioactivity.
Keywords: Titanium; chitosan; hydroxyapatite; infection; local drug release; antimicrobial activity; Engineering; Materials Science